Highly Reversible Aqueous Zinc Batteries enabled by Zincophilic–Zincophobic Interfacial Layers and Interrupted Hydrogen‐Bond Electrolytes - Cao, Longsheng; Li, Dan; Soto, Fernando A.; Ponce, Victor; Zhang, Bao; Ma, Lu; Deng, Tao; Seminario, Jorge M.; Hu, Enyuan; Yang, Xiao‐Qing; Balbuena, Perla B.; Wang, Chunsheng (Angewandte Chemie (International ed.), 2021)
Aqueous Zn batteries promise high energy density but suffer from Zn dendritic growth and poor low‐temperature performance. Here, we overcome both challenges by using an eutectic 7.6 m ZnCl2 aqueous electrolyte with 0.05 m SnCl2 additive, which in situ forms a zincophilic/zincophobic Sn/Zn5(OH)8Cl2⋅H2O bilayer interphase and enables low temperature operation. Zincophilic Sn decreases Zn plating/stripping overpotential and promotes uniform Zn plating, while zincophobic Zn5(OH)8Cl2⋅H2O top‐layer suppresses Zn dendrite growth. The eutectic electrolyte has a high ionic conductivity of ≈0.8 mS cm−1 even at −70 °C due to the distortion of hydrogen bond network by solvated Zn2+ and Cl−. The eutectic electrolyte enables Zn∥Ti half‐cell a high Coulombic efficiency (CE) of >99.7 % for 200 cycles and Zn∥Zn cell steady charge/discharge for 500 h with a low overpotential of 8 mV at 3 mA cm−2. Practically, Zn∥VOPO4 batteries maintain >95 % capacity with a CE of >99.9 % for 200 cycles at −50 °C, and retain ≈30 % capacity at −70 °C of that at 20 °C. A highly reversible Zn anode working at low temperature is achieved by introducing SnCl2 into eutectic ZnCl2 aqueous electrolyte to form a zincophilic–zincophobic interfacial layer on the Zn anode in situ. The bottom layer of Sn facilitates uniform Zn deposition, while the top layer of zincophobic Zn5(OH)8Cl2 H2O facilitates Zn2+ diffusion and avoids Zn dendrites. The eutectic composition enhances the low temperature conductivity.